A case report of small cell ovarian neuroendocrine carcinoma combined with immunochemotherapy. Issue 46 (18th November 2022) - Zhu, Yuan-Xue; Gao, Xiang-Peng; Xin, Lei; Jia, You-Chao
Abstract : Background: Small cell ovarian neuroendocrine (NE) carcinoma is a rare NE tumor with a low incidence, poor prognosis, and no standardized treatment. To date, there have been no clear reports on the efficacy or prognosis of combined immunological and chemotherapy-based approaches in patients with this type of tumor. Methods: We administered the immune checkpoint inhibitor tirelizumab (PD-1 mab), in combination with etoposide and cisplatin chemotherapy (EP), to a patient with small cell ovarian NE carcinoma to examine its efficacy and safety. Results: The evaluation of efficacy was PR for every 2 courses of application, and immunomaintenance therapy was administered after 6 courses of treatment. Conclusion: Our studies indicate that tirelizumab combined with EP, may be an effective treatment for small cell ovarian NE carcinoma.